Intermediate-Term Outcomes of Trapeziectomy With a Modified Abductor Pollicis Longus Suspension Arthroplasty - Brandon E. Earp, MD; Ariana N. Mora, BA; Jacob A. Silver, BS; Kyra A. Benavent, BS; Philip E. Blazar, MD (Journal of Hand Surgery Global Online, 2019)
Purpose: There is limited literature characterizing intermediate-term surgical and clinical outcomes of basal thumb arthritis after trapeziectomy and modified abductor pollicis longus suspension arthroplasty (APLSA). We hypothesized that patients who underwent APLSA would have favorable intermediate-term outcomes. Methods: Patients were contacted after APLSA at a median follow-up of 4.8 years (interquartile range, 3.0–6.0 years). Follow-up clinical evaluation included grip, key pinch, and tip pinch strength. We obtained patient-reported outcomes surveys: visual analog pain score and Disabilities of the Arm, Shoulder, and Hand score. Information on demographics, surgical information, and complications was obtained from the electronic medical record and patient interviews. Results: This study evaluated 66 hands in 60 patients (51 women and 9 men, average age 60.4 years at surgery). At the time of index surgery, 8% of hands had prior ipsilateral surgery (not involving the carpometacarpal joint), 56% had concurrent ipsilateral surgery (35% carpal tunnel release, 32% hemitrapezoid resection, 22% other soft tissue procedures (mucous cyst excision, ganglion cyst excision, or trigger finger release), 5% metacarpal capsulodesis, and 5% metacarpal arthrodesis. Median time between operation and most recent evaluation was 4.8 years (interquartile range, 3.0–6.0 years). Operative hand grip (18.7 ± 11.1 kg), key pinch (4.7 ± 2.1 kg), and tip pinch (3.2 ± 1.7 kg) strength was 94%, 84%, and 86%, respectively, of nonsurgical grip, key pinch, and tip pinch strength. Median (interquartile range) outcomes were a visual analog pain score of 0.0 (0.0–2.0) and Disabilities of the Arm, Shoulder, and Hand score of 9.1 (2.3–26.1). Conclusions: Results at 4.8 years for APLSA demonstrated 84% to 94% grip, key pinch, and tip pinch compared with the contralateral side. Patients experienced little to no pain in the operated joint and minimal disability of the upper extremity at intermediate-term follow-up. Abductor pollicis longus suspension arthroplasty is a favorable procedure for achieving pain relief and functional use associated with basal thumb arthritis. Type of study/level of evidence: Prognostic IV. Key words: abductor pollicis longus, basal joint arthritis, carpometacarpal arthritis, suspensionplasty, trapeziectomy